เภสัชจลนศาสตร์ของยาเซฟไตรอะโซนในผู้ป่วยโรคเบต้า-ธาลัสซีเมีย/ฮีโมโกลบินอี - นวรัตน์ ปัญจสวัสดิ์วงศ์ (จุฬาลงกรณ์มหาวิทยาลัย, 2009)
The purposes of this study were to evaluate pharmacokinetics of intravenous ceftriaxone 1 g once daily in β-thalassemia/hemoglobin E patients, to develop ceftriaxone pharmacokinetic model and to simulate concentration-time curve. Eighteen β-thalassemia/hemoglobin E patients were recruited and subsequently received a single dose of ceftriaxone 1 g by intravenous infusion over 30 min. Blood samples were collected at times 0, 0.25, 0.5, 0.67, 1, 2, 4, 8, 12 and 24 hr after administration of the drug. Plasma ceftriaxone concentrations were assayed by high performance liquid chromatography (HPLC). The results of non-compartmental pharmacokinetic analysis show that the mean value +standard deviation of elimination rate constant (Ke) was 0.0860+0.0146 hr-1, half-life (t1/2) 8.27+1.35 hr, area under the curve (AUCinf) 1544.66+275.75 hr*ug/mL, volume of distribution (Vd) 7847.09+1338.35 mL and ceftriaxone clearance (CL) 667.22+120.04 mL/hr. The most suitable pharmacokinetic model that can describe the pharmacokinetic profile of ceftriaxone concentrations was a two-compartment model as equation Ct = -1306386e-2.3673(t) + 121.12e-0.0847(t) + 1306264.88e-2.3669(t). The simulation of concentration-time curve to determine the time when concentration exceeds the MIC (T > MIC) shows that ceftriaxone 1 g by intravenous infusion over 30 min once daily had efficacy against Salmonella, Streptococcus pneumoniae, Klebsiella pneumoniae, Escherichia coli and Staphylococcus aureus. Nevertheless, free drug concentration had efficacy against Salmonella and Streptococcus pneumoniae. As this dosage regimen of ceftriaxone, it might affect time above MIC value (< 80%). The efficacy of ceftriaxone could be increased by giving higher dose or decreasing the dosing interval or increasing the infusion duration.